DUCT reveals architectural mechanisms contributing to bile duct recovery in a mouse model for Alagille syndrome - Hankeová, Simona; Šalplachta, Jakub; Zikmund, Tomáš; Kavková, Michaela; Van Hul, Noemi; Břínek, Adam; Smékalová, Veronika; Lázňovský, Jakub; Dawit, Feven; Jaroš, Josef; Bryja, Vítězslav; Lendahl, Urban; et al. (ELIFE SCIENCES PUBLICATIONS LTD, 2021)
Organ function depends on tissues adopting the correct architecture. However, insights into organ architecture are currently hampered by an absence of standardized quantitative 3D analysis. We aimed to develop a robust technology to visualize, digitalize, and segment the architecture of two tubular systems in 3D: double resin casting micro computed tomography (DUCT). As proof of principle, we applied DUCT to a mouse model for Alagille syndrome (Jag1Ndr/Ndr mice), characterized by intrahepatic bile duct paucity, that can spontaneously generate a biliary system in adulthood. DUCT identified increased central biliary branching and peripheral bile duct tortuosity as two compensatory processes occurring in distinct regions of Jag1Ndr/Ndr liver, leading to full reconstitution of wild-type biliary volume and phenotypic recovery. DUCT is thus a powerful new technology for 3D analysis, which can reveal novel phenotypes and provide a standardized method of defining liver architecture in mouse models.

Organ function depends on tissues adopting the correct architecture. However, insights into organ architecture are currently hampered by an absence of standardized quantitative 3D analysis. We aimed to develop a robust technology to visualize, digitalize, and segment the architecture of two tubular systems in 3D: double resin casting micro computed tomography (DUCT). As proof of principle, we applied DUCT to a mouse model for Alagille syndrome (Jag1Ndr/Ndr mice), characterized by intrahepatic bile duct paucity, that can spontaneously generate a biliary system in adulthood. DUCT identified increased central biliary branching and peripheral bile duct tortuosity as two compensatory processes occurring in distinct regions of Jag1Ndr/Ndr liver, leading to full reconstitution of wild-type biliary volume and phenotypic recovery. DUCT is thus a powerful new technology for 3D analysis, which can reveal novel phenotypes and provide a standardized method of defining liver architecture in mouse models.
DUCT reveals architectural mechanisms contributing to bile duct recovery in a mouse model for Alagille syndrome
Keywords: Alagille syndrome; MicroCT; cholangiopathy; human; mouse; physics of living systems; regenerative medicine; resin; stem cells; vasculature.; Alagille syndrome; MicroCT; cholangiopathy; human; mouse; physics of living systems; regenerative medicine; resin; stem cells; vasculature.